Heat Transfer: Volume 3 2003
DOI: 10.1115/ht2003-47050
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Flow and Heat Transfer in Rectangular Micro-Channels

Abstract: Knowledge of flow pattern and flow pattern transitions is essential to the development of reliable predictive tools for pressure drop and heat transfer in two-phase micro-channel heat sinks. In the present study, experiments were conducted with adiabatic nitrogen-water two-phase flow in a rectangular micro-channel having a 0.406 × 2.032 mm cross-section. Superficial velocities of nitrogen and water ranged from 0.08 to 81.92 m/s and 0.04 to 10.24 m/s, respectively. Flow patterns were first identified using high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The above results can be presented in a form of general expressions for the critical channel height and the corresponding maximum critical gas superficial velocity: - (27), implying that the range of gas flow rates for which stratified flow with a smooth interface can be maintained in field operations, which are associated with large channel sizes and elevated pressures, is much smaller than that obtained in lab scale experiments. Similarly, the range of stable (smooth) stratified flow when downscaling to micro channels significantly diminishes, which is in a general agreement with experimental findings (e.g., Kawahara et al, 2002, Qu et al, 2004, Ide et al, 2007.Note that the critical Fr and Re are however dependent on the viscosity ratio and should be identified for the particular gas-liquid system under consideration.…”
Section: B Gas-liquid Systemssupporting
confidence: 87%
“…The above results can be presented in a form of general expressions for the critical channel height and the corresponding maximum critical gas superficial velocity: - (27), implying that the range of gas flow rates for which stratified flow with a smooth interface can be maintained in field operations, which are associated with large channel sizes and elevated pressures, is much smaller than that obtained in lab scale experiments. Similarly, the range of stable (smooth) stratified flow when downscaling to micro channels significantly diminishes, which is in a general agreement with experimental findings (e.g., Kawahara et al, 2002, Qu et al, 2004, Ide et al, 2007.Note that the critical Fr and Re are however dependent on the viscosity ratio and should be identified for the particular gas-liquid system under consideration.…”
Section: B Gas-liquid Systemssupporting
confidence: 87%
“…Classical descriptions of the latter point to nucleation of a number of bubbles that grow, depart, and coalesce with one another, resulting in a several possible flow regimes, bubbly, slug, churn, and annular. However, in small channels, a nucleating bubble can quickly grow to engulf the entire cross-sectional, and as the heat flux is increased, a slug flow pattern evolves as the initial bubble grows axially by evaporation [14,15]. Fig.…”
Section: Bubble Growth In Small Channelsmentioning
confidence: 98%
“…Flow field flooding occurs at relatively low air/H 2 stoichiometry, for which a plug/slug flow regime has been observed in operating fuel cells [6e9]. From microscale two-phase flow studies [10,11] performed in semi-triangular and rectangular microchannels having a hydraulic diameter of 1 mm, it can also be concluded that a plug/slug flow regime is most likely to occur at low gas flow rates that correspond to low stoichiometry ( 2). Twophase flow regimes in the gas channels and their relevance for the PEM fuel cell operation was reviewed by Anderson et al [1], who concluded that more optimization work is still needed.…”
Section: Introductionmentioning
confidence: 99%